An Analysis of Mathematics Learning from Homes of Grade 1 Elementary School Students During the Covid-19 Pandemic - Andrea Reza; Delfi Eliza (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2021)
The Covid-19 pandemic has affected all important sectors such as education. This incident made parents take part in helping children learn from home including learning mathematics for grade 1 SD. This study aimed to analyze mathematics learning from home during the Covid-19 pandemic in grade 1 students at Al Ishlah Bukittinggi Islamic Elementary School in the 1st semester of the 2020/2021 school year. This type of research used descriptive qualitative. Collecting data used the method of documentation, interviews, questionnaires and observation sheets. The results of the study aim to see the learning activities, processes and expectations of children, parents and teachers during the Covid-19 Pandemic.